Uncovering Co-Operators Entrepreneurial Traits: An Empirical Investigation - Bakkar, Mohammed; El Khaddar, Hafid; El Meskine, Lahcen; Chakir, Ahmed (Journal of Entrepreneurship, Business and Economics; Vol 8 No 2 (2020), 2020)
In light of studying the social entrepreneurship ecosystem in Morocco, this paper aims at providing a summary regarding a range of characteristics and entrepreneurial traits among cooperatives’ members (co-operators). It is also about interpreting the faculty of existing literature to examine motives and antecedents leading to the development and the maintenance of entrepreneurial spirit among co-operators. The methodology followed is based on Geert Hofstede’s (1980, 1994) empirical framework regarding national cultures as well as the research of both Bachelet et al (2005), and Shepherd & Douglas (1997) as regards to the impact of psychological and socio-cultural factors on entrepreneurs’ personality and spirit. Cooperatives business is in an area of growing significance in Morocco. Nowadays we count more than 27000 cooperatives (15000 in 2015) where the regions of south have the major concentration of cooperatives (35%). The main source of data was collected through regional co-operators quantitative survey conducted among a group of 15 southern cooperatives in various sectors involving 114 co-operators. Investigated topics and chosen variables were decided beforehand, through a national expert's survey, and conducting interviews with 24 national experts in fields related to cooperative entrepreneurship. This is in order to having their perspectives on relevant co-operators framework settings, motivations, skills, personal traits, etc. Based on the respondents’ answers, we’ve tried to understand the type of organizational culture within their specific entities. The results emphasized the preeminence of collective culture, a low aversion to risk and synchronous behavior towards time as well as the positive impact of entrepreneurial self-efficacy motivations such as working within a team and seizing opportunities. Outcomes underline the importance of social environment on the entrepreneurial expression concerning co-operants, as well as significant attitudes variables such as autonomy, initiative and need for fulfillment. The study recommends that co-operators should identify their unique behavior, explore ways to improve and get additional skills that will help them become more proactive towards issues of their domain. Overall, this paper provides one of a few projections of entrepreneurship assumptions on cooperatives field in Morocco and offered one glimpse into nature of cooperative members in the country. We expect this may help researchers, practitioners and policy-makers understand possible improvement opportunities for cooperative field and social entrepreneurship in general. Research paper Keywords: Psychological; Socio-cultural, Traits; Entrepreneurial spirit; Organizational culture Reference to this paper should be made as follows: El Khaddar, H., Bakkar, M., El Meskine, L., & Chakir, A. (2020). Uncovering Co-Operators Entrepreneurial Traits: An Empirical Investigation, Journal of Entrepreneurship, Business and Economics , 8 (2), 1–35.